Computational modelling and data analysis on the virulence of influenza viruses - Zhou, Xinrui (Nanyang Technological University, 2020)
Influenza virus, a rapidly evolving contagious virus causing seasonal flu, has been circulating globally for centuries. The first recorded influenza pandemic was in 1918, claiming at least 50 million lives. Until 1933, influenza viruses were isolated from human for the first time, proving that influenza is caused by a virus rather than a bacterium. Seasonal influenza has caused substantial social and economic burden worldwide, affecting school attendance, work absenteeism, industrial productivity, etc. It mainly infects the respiratory system and can cause pneumonia, severe complications, or deaths, especially among people at high risks. Flu vaccines have been designed as primary prevention to help defense viral infection in advance. However, the rapid and continuous evolution of influenza raises the challenge to prepare vaccine candidates matching the antigenicity of dominant circulating influenza viruses for the next season. Therefore, it is in urgent demand to characterize and predict the antigenicity of influenza in advance.